Trust in the Network of Food Diversification Policy Implementation in Bone Regency - Hartina, Hartina; Alwi, Alwi; Susanti, Gita (Departemen Ilmu Administrasi FISIP UNHAS, 2020)
Trust that is well built in the policy-making process in network organizations gives birth to an effective policy outcome in the form of decreased assumption levels. This research method uses a qualitative approach and a case study strategy to explain trust in the implementation of food diversification policies. The data was collected through in-depth interviews and observations. Data processing and analysis techniques are carried out in three stages, namely: data reduction, presentation and conclusion drawing. The informants in this study were as follows: a) Chair of the Women Farmers Group b). sub-district extension team; d) District extension team.The results showed that the trust that occurred in the interaction of actors, in this case the Food Security Service, Extension Officers and the Women Farmers Group in the implementation of food diversification policies in Bone Regency was not effective. This can be shown that there is no mutual agreement that can be used as a rule of the game for the actors involved in implementing this policy. Opportunistic behavior is a sub-concept that assesses the presence and absence of trust, which is not identified in this study, because there is no mutually agreed upon rule of the game. Then, the actors' good will trust does not emerge because they are still designing and running their respective programs. Therefore, the implementation of the diversification policy requires trust between them so that the performance of this policy can be realized.